WAKTU PENYIMPANAN TROMBOSIT TERKAIT JUMLAH DI KONSENTRAT TROMBOSIT - Raehana Samad; Agus Alim Abdullah; Kusriny A.P.; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
The transfusion of thrombocyte concentrate is one of the important medical approaches to make the platelet count raised in patients with thrombocytopenia. The TC could change during the storage process, so the in vitro storaging should be considered to minimalize the alterations on the platelet count. The study was aimed to know the impact of storage time to maintain the platelet count stability in TC of transfusion blood by evaluating it. A study with Time Series design was performed in 30 samples of TC of transfusion blood collected from 30 blood donors. The samples was collected from the bag tube of TC and the test is performed as soon as possible by using haematological analyzer (Sysmex KX-21) with an impedance method, the rest of the samples was stored in an agitator on 22±2°C to perform a repeated count on day 5th and 7th. The collected data was analyzed with “Paired T Test”. The results of this study showed that the platelet count in TC of transfusion blood was decreased in the fifth day compared to the first day, but the decreased matter is insignificant, statistically (p=0.13). While after seventh (7) day, the platelet count is decreased significantly (p=0.00). The researchers concluded that the storage of TC for seven (7) days could not maintain the stability of the platelet count of the transfusion blood. There fore is suggested, a further study to evaluate the impact of storage time on platelets viability. So the quality of platelets in TC of transfusion blood can be evaluated.